Corporate Reputation Management: A Case Study of Courier Service Provider - Norhaznan Nor Farzanah (Tecno Scientifica Publishing, 2021)
One of the most significant intangible organisational assets is reputation. It's a complicated phenomenon that needs to be handled carefully. In fact, it has been proven that an organization's reputation is a prerequisite for individual stakeholders' willingness to participate in a relationship with it. This essay seeks to clarify the communication tactics that should be utilised to restore an organization's reputation that has been harmed by a problem. A case study of postal currier services was used to demonstrate how a problem might lead to a negative reaction from stakeholders. In maintaining an organization's reputation, the essay stated that addressing the issue immediately, developing inclusivity among employees, and organisational commitment as a corporate citizen are all vital.